Penerapan Digital Marketing Sebagai Strategi Pemasaran Pada UMKM Pakan Super Klasik - Cindy Clarissa Quenby; Maharani Ikaningtyas (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The rapid development of internet technology in the current era has changed the paradigm of traditional marketing into digital marketing using internet media, which is known as digital marketing. Digital marketing plays an important role in the success of MSME marketing because it allows analysis of new target markets, consumer behavior and product information. However, only a few MSMEs have an understanding of this digital technology-based marketing strategy. As a form of contribution to community service, students from UPN